The System for Keeping Records of Radio and TV Receivers based on the Java J2ME Platform - Kuk, K.; Rančić, D.; Spalević, P.; Dimić, G. (Elektronika ir Elektrotechnika, 2010)
This work gives an overview of structures and organization of a GPS application based on J2ME architecture, which was applied in a system for keeping a record of radio receivers. Development of a mobile GPS application based on the J2ME platform usage has been launched for the needs of the RATEL company. It also combines various technologies, such as GPS, Google Maps, Ajax and Web as a distributed system, in order to show the location, i.e. position of an unknown frequency broadcaster on a digital map in mobile phone.